The Impact of Project Based Learning (PBL) Method on Motivation and Interest in English Learning Among Eleventh Graders at SMAN 1 Karangrejo - Safina Pramas Dinda; Ayu Rizki Septiana (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is driven by the principles of Project Based Learning (PJBL). PJBL is an educational approach that utilizes real-world problems as the starting point for integrating new knowledge. The research question posed is whether the PJBL method affects motivation and interest in learning English among eleventh-grade students at SMAN 1 Karangrejo. The objective is to examine the impact of PJBL on motivation and interest in English learning at this school. This study employs a quantitative approach, specifically a non-experimental quasi-regression design, with data collection conducted via a questionnaire using purposive sampling. Data analysis involves descriptive statistics to determine mean values, followed by testing for normality assumptions. If the data meets normality criteria, Pearson correlation analysis is used to examine relationships between variables (X and Y1, X and Y2). Additionally, simple linear regression tests the effects of variables Y1 and Y2 on X. The findings indicate that implementing PJBL in English language education for eleventh-grade students is expected to enhance both motivation and interest in learning at SMAN 1 Karangrejo.